2018
DOI: 10.1016/j.jneumeth.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Automatic quantification of juvenile zebrafish aggression

Abstract: This setup appears to be suitable to screen for drugs that decrease zebrafish aggression as a first step toward developing novel treatments for this behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 48 publications
(76 reference statements)
0
19
1
Order By: Relevance
“…The altered behavioural phenotype of adult hrh3 −/− fish and brain region‐specific differences in hrh3 expression between larvae and adults 25 raises the question whether larval hrh3 mutant fish show similar behavioural alterations. Larval zebrafish do not display aggressive‐like behaviour before 30 dpf, 31 however, assays to measure locomotion and anxiety‐like behaviour in early life stages have been established 32 . When tested in the larval unstimulated locomotion assay, we found that hrh3 −/− larvae move less than age‐matched WTs ( U = 45.0; P = .004; Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The altered behavioural phenotype of adult hrh3 −/− fish and brain region‐specific differences in hrh3 expression between larvae and adults 25 raises the question whether larval hrh3 mutant fish show similar behavioural alterations. Larval zebrafish do not display aggressive‐like behaviour before 30 dpf, 31 however, assays to measure locomotion and anxiety‐like behaviour in early life stages have been established 32 . When tested in the larval unstimulated locomotion assay, we found that hrh3 −/− larvae move less than age‐matched WTs ( U = 45.0; P = .004; Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…In this study we show for the first time that genetic and pharmacological manipulation of the Hrh3 receptor reduces aggression in the MIA test. This assay makes use of the fact that zebrafish do not recognize their own mirror image and fight it 31 . Similar to real fights, zebrafish attack and bite the mirror opponent, but there is no risk of harm which favours this test over dyadic fights from an ethical perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Studying experimental impulsivity and other ICD‐related traits is a rapidly developing multidisciplinary field that integrates neurobehavioral processes at multiple levels of analysis to improve our understanding of these severely debilitating and disruptive illnesses (Rochat, Billieux, Gagnon, & Van der Linden, 2018; Winstanley, Olausson, Taylor, & Jentsch, 2010). The zebrafish emerges as an important novel sensitive animal model organism that enables assessing impulsivity, aggression and locomotion in both larval and adult fish (Carreño Gutiérrez, Vacca, Pons, & Norton, 2018; Parker, Ife, et al, 2013). Sex is another biological variable that can strongly influence zebrafish ICD‐related traits, such as aggressive behavior and locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Automated protocols (e.g., 5‐CSRTT and other tasks listed in Table 2) and multiple commercial or open‐access software tools for behavioral assessment in zebrafish enable continuous monitoring of various impulsive and aggressive phenotypes discussed above (Carreño Gutiérrez et al., 2018; Parker, Ife, et al, 2013). Using the 5‐CSRTT, for example, to screen for the effects of novel or repurposed drug compounds, may contribute to development of new therapies for ICDs.…”
Section: Discussionmentioning
confidence: 99%
“…This could mean that the aggression and shoaling phenotype are separate entities, or that there is a different basis of social behaviour in juvenile and adult fish. For example, the neural circuits that control shoaling may mature earlier than those that underpin aggression permitting the social phenotype to be expressed more precociously 45,46 .…”
Section: Discussionmentioning
confidence: 99%